CAPACITY BUILDING NEEDS OF FARMERS FOR SUSTAINABLE CROP PRODUCTION - Muhammad Saleem; Samrat Sikdar; Syed Taimoor Shah; Sana Shaukat (Policy Journal of Social Science Review, 2026)
Capacity building is a key factor in sustainable crop production, as it improves farmers' knowledge and skills, and their capacity to make decisions. Although agricultural extension programs are available in Pakistan, there is a paucity of evidence regarding farmers' priority training requirements for sustainable farming, and especially in the climate sensitive districts of the southern Punjab. The present study aimed to evaluate the capacity-building requirements of farmers to gain sustainable crop production in Muzaffargarh and Dera Ghazi Khan districts and to explore the socioeconomic factors related to the capacity-building requirements for sustainable crop production. A quantitative cross sectional survey design was used and the primary data was obtained by conducting face to face structured interviews with 140 farmers selected by multistage sampling. Descriptive statistics, independent-samples t-test, one-way ANOVA, chi-square test, Pearson correlation, and multiple regression analysis with IBM SPSS Statistics was used to analyze data. The results showed that water conservation and irrigation management (Mean = 4.42), Integrated Pest Management (IPM) (Mean = 4.35) and climate-smart agriculture (Mean = 4.21) were the most critical capacity building needs, suggesting farmers' awareness of water scarcity, pests, and climate variability. Organic farming (Mean = 3.05) and marketing and value addition (Mean = 3.31) were given a relatively low priority. There was significant difference between the two districts (t = 2.11, p = 0.037) and across education level (F = 5.29, p = 0.006) in overall training needs. Pearson correlation analysis revealed that age (r = −0.187, p = 0.027) and education (r = −0.241, p = 0.004) were negatively related to the overall capacity building needs of farmers. Multiple regression analysis also showed that education (β = −0.263, p = 0.001) and age (β = −0.176, p = 0.021) was significant when used independently to predict training needs, while farming experience and land holding were not significant. The study found that extension approaches cannot be uniform and need to be based on capacity building interventions that are demand-driven and location-specific for sustainable crop production in southern Punjab. Training should be given preference for water management, IPM and climate smart agriculture to improve technology adoption, climate resilience and long term sustainability of agriculture by adapting training methods to farmers' education level. Keywords: Capacity building, sustainable crop production, integrated pest management, water conservation